Evaluation of adenosine deaminase activity in serum and pleural fluid of pulmonary tuberculosis patients with pleural effusion - Malempati, Uma D.; Medooru, Kusuma K. (International Journal of Research in Medical Sciences, 2018)
Background: In endemic regions, a high adenosine deaminase (ADA) activity in lymphocyte predominant exudate is a valuable adjunct in diagnostic evaluation and treatment initiation in tuberculous pleural effusion. Tuberculosis is highly endemic in India, requiring prompt diagnosis, effective treatment and control of the disease. The present study was aimed to evaluate the serum and pleural fluid ADA activities in pulmonary tuberculosis patients with pleural effusion. Methods: This study includes a total of 240 subjects; 40 pulmonary tuberculosis patients (PTB), 40 PTB with pleural effusion (PE), 40 PTB treated for one month, 40 healthy controls, 40 transudative PE patients and 40 nontuberculous exudative PE patients, between 20-70 years of age. ADA activity was estimated by the Guisti-Galanti method along with routine parameters in all study subjects. Results: Serum ADA activity was significantly higher (p<0.001) in PTB with PE (37.68±12.42U/L) than healthy controls (12.15±5.38U/L), transudative PE (22.43±9.12U/L), nontuberculous exudative PE (16.92±4.98U/L) and treated PTB (19.39±4.54U/L). Pleural fluid ADA activity was significantly higher (p<0.0001) in PTB with PE (78.94±36.75U/L) than in transudative PE (11.25±3.12U/L) and nontuberculous exudative PE (17.56±10.42U/L). ADA activity was significantly higher (p<0.001) in pleural fluid than serum in PTB with PE. Lymphocyte percentage was significantly higher (p<0.001) in pleural fluid (86.57±9.64) than peripheral blood (37.48±8.49) in PTB with PE. Conclusions: The pleural fluid ADA activities were elevated in lymphocyte predominant exudates of PTB patients with PE from endemic regions, prompting treatment initiation in high suspicion cases with elevated ADA activity.